Diachronic phenomenology: A methodological thread within media ecology. Issue 1 (1st March 2014) - Anton, Corey
This article identifies and outlines a method of thought and line of research that can be found throughout media ecology. The methodology and research line, 'diachronic phenomenology', explores the many ways that conscious life and social organization (in its essential dimensions, modalities, properties and functioning) resonates with particular environments and media forms, and correspondingly grows, develops and becomes itself. The article thus synthesizes and co-adapts media ecology and phenomenology: media ecology benefits from more robust phenomenological grounding and methodological considerations, while phenomenology benefits from recognizing how various noetic and eidetic economies, as well as invariant features of contemporary life, have been culturally and historically effected and affected by social environments and communicative forms (writing, currency, mirrors, clocks, drugs, etc.). The article walks through a wide range of samples and illustrations and then briefly identifies possible future directions by considering recent developments within the fields of brain science and embodied cognition.